From A… to… Z(OOR): The Clinical Spectrum of Acute Zonal Occult Outer Retinopathy. (4th July 2018) - Wang, Margaret; Sadaka, Ama; Prager, Thomas; Lee, Andrew G; Pellegrini, Francesco; Cirone, Daniele; De Simone, Luca; Cimino, Luca
ABSTRACT: Acute idiopathic blind spot enlargement (AIBSE) is often caused by Acute Zonal Occult Outer Retinopathy (AZOOR), an outer retinal disease. We report two illustrative cases of AZOOR. The first one was a 21-year-old white female who presented with a scotoma and "shimmering lights" in her left eye. In the second case, a 73-year-old white female was referred for evaluation of a "bitemporal hemianopsia" that started years prior, with no clinical significant photopsias. To our knowledge, case two is the longest documented duration of bilateral, progressive, and chronic, idiopathic, enlargement of the blind spot (CIBSE) documented in the English language ophthalmic literature.